Estudo das alterações comportamentais e bioquímicas induzidas pela exposição ao Hg (II) sobre o sistema antioxidante e vias de sinalização celular em Drosophila melanogaster - Paula, Mariane Trindade de (2012)
Mercury (Hg) consists in a heavy metal with toxicological relevance whose contamination is mainly attributed to anthropogenic activities, leading to environmental contamination. It is known that an induction in oxidative stress caused by increased production of reactive oxygen species and/or decrease in antioxidant enzymes activity and a modulation of phosphorylation of proteins that participate in processes of cellular signaling transduction, as Mitogen-Activated Protein Kinases (MAPKs) represent molecular mechanisms implicated in Hg toxicity in rodents and other vertebrates. Studies from the literature have been pointing Drosophila melanogaster as an organism with considerable potential to be used as a bio indicator organism to monitoring the presence of environmental contaminants, presenting biochemical and behavioral effects in response to contaminants similarly to those observed in mammals. Thus, our results showed that HgCl2, when incorporated through the diet with sucrose in D. melanogaster, causes a significant decrease in viability of flies from 24h in a concentration dependent manner. Moreover, after 48h of exposure, the flies treated with Hg 100μM presented deficits in locomotor performance, decrease in the activity of enzymes: acetylcholinesterase (AChE), glutathione peroxidase (GPx) and Superoxide dismutase (SOD), without alteration in catalase activity (CAT). In this study, gene expression of D. melanogaster was evaluated by the method of Real-Time PCR. It was observed that mRNA levels of SOD, CAT and NF-E2-associated factor 2 (Nrf2) were not altered by Hg (II) treatment when compared to the control group, however, Hsp83 expression was10 times increased. Additionally, from 6h of treatment with Hg (II) 100 μM it was verified an induction of lipid peroxidation and oxidative stress, these effects persisted until 48 h of treatment. In the present study, the amount of Hg in the treated and control flies was measured and expressed in μg Hg / g tissue. It was observed that the flies treated for 48h with HgCl2 (100 μM) presented higher levels of Hg than the control group (100 times increase). With regard to the modulation of signaling pathways by Hg (II) treatment, the metal caused an increase in phosphorylation levels of ERK and JNK without altering phosphorylation of p38 as well as the total content of these proteins. Hg (II) exposure caused an induction of PARP cleavage, indicating an induction of apoptotic cell death. In conclusion, the data obtained over this work draw attention to the Hg (II) toxicity and help to extend the knowledge about the mechanisms involved in the toxicity of this metal in invertebrates. In addition, this study points the antioxidant system and modulation of specific signaling transduction pathways as common mechanisms mediating the toxicity of Hg (II) in vertebrates and invertebrates.